(3TQM GdeVfhf Hg Ydi ZjQ Cgdgs - (3dYHjO Gddg Hf YHO GdcGai Hf YHO GdeLjO GdYHjOis; (3YHO GdhgGH Hf EHQGgje Hf YHO GdhgGH GdNRQLj GdRfLGfj,J (B655 (3g` s
(3ChdgG (B:s
(3hCeG HYO adeG QCjJ hdY GdeMUdjf hTZa GdeJYdejf Ydi bQGAI GdCHjGJ GdJi YHO GdhgGH Hf EHQGgje GdNQLi GdRfLGfi eeG CNJGQgG ef GdOhGhjf GdZQHjI s
(3BNQgG (B:s
(3aHPdc GdSeY hGdHUQ ai ebGHdg aVdce hEPG hUdJ Edi BNQ GdCHjGJ GdeNJGQg bWYJ GdcdGe hbO aQZJ efg s
(3GdCTYGQ HGdMeQgs
(3hHChdgG Jedc eDQN Sfg (B1010 (3g`s
(3hghTQM CHjGJ GfJNHgG YR GdOjf YHO GdhgGH Hf EHQGgje GdNQLi GdRfLGfi haQZgG GdTGQM ef JCdjag SfI (B724s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs